Cost Efficiency, Total Assets, and Profitability: Evidence from Islamic Bank - Sholikha Oktavi Khalifaturofi'ah (Jurnal Keuangan dan Perbankan, 2018)
Inefficiency is one of the factors that can decrease the bank’s health. Efficiency was very important for banking. Efficient banking will increase total assets and profitability. This study examined the cost efficiency of sharia banks and their effects on total assets and profitability. This study aimed to analyze the effect of cost efficiency and other financial ratios on total assets and profitability. By using a stochastic frontier approach, it was found that the average cost efficiency level in sharia bank was 85.18 percent. Furthermore, by using a panel regression method in 12 sharia banks, it was found that cost efficiency had a negative effect on total assets but did not affect the profitability of sharia banks. In addition to cost efficiency, CAR also had negative effects on total assets. FDR and NPF had a negative effect on profitability which proxied by ROA while profitability proxied by ROE negatively affected by NPF. Sharia banking should pay attention to the level of cost efficiency, capital adequacy, and financing quality in order to increase total assets and profitability.JEL Classification: G31, G32, G34DOI: https://doi.org/10.26905/jkdp.v22i4.2218